1986
DOI: 10.1063/1.1138539
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic suspension systems with digital controllers

Abstract: Interruptdriven digital controller for a magnetic suspension system Rev. Sci. Instrum. 60, 456 (1989);Single-axis magnetic suspensions, using optical position sensing and dc electromagnets, have been developed with eight-bit-word digital controllers that replace the familiar analog phase-advance or proportional-plus-derivative circuits. Control algorithms are obtained by a simple curve-fitting approach to signals sampled at constant rates. Stable suspension has been demonstrated at sampling rates down to 75Hz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…) and the PWM frequency ( ) are two crucial parameters for the dynamic performance of the high-speed PEMS transportation system, e.g., the disturbance rejection and the gap tracking 15 . In the literature, is usually set from 75 Hz to 2 kHz 12, [16][17][18] for the digital controller, whereas is usually set from 10 kHz to 20 kHz 3,[11][12][13] . Generally, is at least 5-time smaller than .…”
Section: Introductionmentioning
confidence: 99%
“…) and the PWM frequency ( ) are two crucial parameters for the dynamic performance of the high-speed PEMS transportation system, e.g., the disturbance rejection and the gap tracking 15 . In the literature, is usually set from 75 Hz to 2 kHz 12, [16][17][18] for the digital controller, whereas is usually set from 10 kHz to 20 kHz 3,[11][12][13] . Generally, is at least 5-time smaller than .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in low-resource microcontrollers, the lack of floating-point unit (FPU) represents a disadvantage in the implementation of digital controllers; in other words, when floating-point operations are required to be performed in a microcontroller without FPU, a lot of machine cycle times are consumed; as a consequence, the execution time to complete the operation will be larger than the time consumed by the control algorithm to finish an iteration. Some authors have proposed techniques to implement control algorithms by optimizing the execution time in low-resource microcontrollers; for example, Carmichael et al [5], in 1986 constructed a lookup table to cover all possible floating-point multiplications reducing the execution time. In 2004, Abbadi [1] readjusted the input signal scale with a complex analog interface with specific gain to convert floating-point numbers to integer numbers.…”
Section: Introductionmentioning
confidence: 99%
“…They noted that the particular digital control algorithm used was successful but not quite as qood as the corresponding analog one. Carmichael, et al [6] reported the use of digital controls in a single axis vertical support for a 1 in diameter ball. Scudiere, et al [7] employed a microprocessor based digital control system to support small steel spheres and small vertical rotors with masses up to 90 grams.…”
Section: Introductionmentioning
confidence: 99%